Research Progress of Exercise Therapy in Lipid Metabolism - Wu Yuwei (International Journal of Education and Humanities, 2024)
Persistent elevation of blood lipids promotes the accumulation of cholesterol in the vascular walls, leading to atherosclerosis, which is a key risk factor for serious cardiovascular and cerebrovascular diseases such as coronary heart disease and stroke. Hyperlipidemia is mainly classified into two subtypes: primary and secondary. Its occurrence is influenced by multiple factors, including genetic predisposition, dietary habits, liver metabolism abnormalities, insulin resistance, and oxidative stress. Aerobic exercise has a significant positive impact on hyperlipidemia by promoting fat oxidation and reducing lipid parameters. Resistance training effectively improves lipid metabolism by increasing muscle mass and enhancing basal metabolic rate. Although several sports medicine organizations worldwide have advocated the use of exercise prescriptions to prevent and treat chronic diseases, this approach has not been widely and effectively applied in the prevention and treatment of hyperlipidemia. This paper aims to review the pathogenesis of hyperlipidemia and explore the role of exercise in lipid regulation, advocating for the achievement of fat reduction goals through physical activity to provide a scientific basis for the treatment of hyperlipidemia